Biological activities of pyrazoline-indole based Re(I) carbonyls: DNA interaction, antibacterial, anticancer, ROS production, lipid peroxidation, in vivo and in vitro cytotoxicity studies. (1st October 2020) - Varma, Reena R.; Pandya, Juhee G.; Vaidya, Foram U.; Pathak, Chandramani; Bhatt, Bhupesh S.; Patel, Mohan N.
Abstract: Hetero mononuclear rhenium(I) metal complexes (I-V) using different substituted indole-pyrazoline based ligands were synthesized and characterized by spectroscopic and analytical methods. The binding of the rhenium complexes to Herring sperm DNA was monitored by UV spectroscopy, viscosity measurements, and molecular docking studies; groove binding was suggested as the most possible mode and the DNA-binding constants of the complexes were evaluated. In vivo and in vitro cytotoxicity of compounds were evaluated against the brine shrimp and S. cerevisiae cells. An antimicrobial study was carried out by estimating MIC (Minimum Inhibitory Concentration) against two Gram-positive and three Gram-negative bacteria. All synthesized complexes are biologically more active than the corresponding ligands. The anti-proliferation activity of complexes was evaluated on MCF-7, HCT116, and A549 cancer cells by MTT assay. The toxicity profile of synthesized compounds was confirmed by H2 O2 production by reactive oxygen species. The increased concentration of lipid peroxidation end products increased free radicals, which enhancing the oxidative stress level in living organisms and results in cell death. Highlights: Synthesis and characterization of pyrazoline-indole based Re(I) carbonyls. Cell anti-proliferation activity on MCF-7, HCT116 and A549 cell lines. Complexes have potent anticancer activity than standard drugs carboplatin and oxaliplatin. DNA interaction, antibacterial, in vitro and in vivo cytotoxicity studies.